Analysis of Caffeine by HPLC Methods and Recent Advances - Patil Pandurang N. (Pharmaceutical Research: Recent Advances and Trends Vol. 9, 2024)
Coffee, tea, and soft drinks are very commonly used beverages all over the world. Caffeine stimulates the central nervous system and promotes relaxation, myocardial stimulation, and recreational activities. It can provide energy, decrease fatigue, and enhance performance. Caffeine has medicinal properties so it can be used along with other drugs for headaches, stimulation, and muscle relaxants. Caffeine is useful with certain limits but an overdose of caffeine starts side effects on the human body. Various instrumental methods can be used to analyze caffeine in plants, coffee, tea, soft drinks, and pharmaceutical formulations in the presence of other drugs. Different techniques are available to determine caffeine like UV spectrophotometry, HPTLC-UV, capillary electrophoresis-UV, flow injection analysis, electrospray ionization (ESI), Gas chromatography, NIRS and Mass spectrometry in various samples along with pharmaceutical preparations. HPLC methods are the most common, reliable methods used for the analysis of caffeine used in industries. HPLC can accurately and precisely detect caffeine in extremely low concentrations and highly complex materials. This review summarizes various HPLC methods used for caffeine analysis in samples and complex mixtures. Various chromatographic conditions are summarized in tabular form such as different columns, mobile phases, detectors, flow rates, and a variety of samples. Recent advances in technologies with the use of green chemicals for sustainable methods for caffeine analysis in different complex matrix materials have been studied.